Evaluating patient turn effectiveness using turn-assist technologies. (2nd January 2020) - Budarick, Aleksandra R.; Moore, Christopher; Fischer, Steven L.
Abstract: Pressure ulcers are commonly developed in bedridden patients due to prolonged pressure on bony prominences. Turn-assist support surfaces have been developed to help reposition patients to redistribute interface pressure. The aim of this study was to determine if turn-assist technologies confer benefits to patients relative to manual turning, and to determine if different turn-assist functionalities influence patient outcomes differently. Interface pressure (contact area, average and peak pressure) and patient turn quality metrics (turn angle and repeatability) were recorded during manual and facilitated turns on two different turn-assist hospital beds at initial patient position, turn-assist (maximal mattress inflation) and final patient position. Manual turns produced the most repeatable turn angles, and closest to the recommended 30° compared to both turn-assist surfaces. Interface pressure differences between surfaces were most prominent in the pelvis region across all three time points. Overall, turn-assist surfaces produced interface pressure outcomes similar to manual turning, but manual turning produced more repeatable and optimal patient turn angles. Different turn-assist surfaces achieved different patient turn angles, so functionalities should be examined before device implementation.